PENELITIAN PENGEMBANGAN: INSTRUMEN IDENTIFIKASI HAMBATAN BELAJAR PADA ANAK BERBAKAT USIA 4 TAHUN - Pahlawaty, Neddyana; Damanik, Prince Clinton Immanuel Christian; Ningsih, Kholifatul Novita (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Parents' and teachers' unrecognized talents and learning difficulties in children between the ages of two and five often cause children to lose opportunities to develop according to their potential and talents. Parents' and teachers' lack of understanding of the learning difficulties experienced by gifted children causes them to fail to achieve their potential. To reduce the failure rate among gifted children, researchers conducted development research using the Hannafin and Peck Research and Development model, as well as data collection techniques through observation, interviews, and documentation studies at the Bloom Child Development Center in Bekasi City. The results of this study show that the instruments developed are easy for teachers at the Bloom Child Development Center in Bekasi City to understand and use in identifying learning difficulties in gifted children at the perceptual-motor stage of development (2-5 years). These instruments consist of: instruments for identifying gifted children and identifying learning development at the perceptual-motor and cognitive stages through the elaboration of theories of giftedness and child development.